Macroeconomic Stability in Resource-Rich Countries : The Role of Fiscal Policy - Bova, Elva (IMF Working Papers; Working Paper ;, 2016)
Resource-rich countries face large and persistent shocks, especially coming from volatile commodity prices. Given the severity of the shocks, it would be expected that these countries adopt countercyclical fiscal policies to help shield the domestic economy. Taking advantage of a new dataset covering 48 non-renewable commodity exporters for the period 1970-2014, we investigate whether fiscal policy does indeed play a stabilizing role. Our analysis shows that fiscal policy tends to have a procyclical bias (mainly via expenditures) and, contrary to others, we do not find evidence that this bias has declined in recent years. Adoption of fiscal rules does not seem to reduce procyclicality in a significant way, but the quality of political institutions does matter. Finally, non-commodity revenues tend to respond only to persistent changes in commodity prices.